Chicken-derived tripeptide KPC (Lys-Pro-Cys) stabilizes alcohol dehydrogenase (ADH) through peptide-enzyme interaction. (1st May 2022) - Xiao, Chuqiao; Toldrá, Fidel; Zhou, Feibai; Mora, Leticia; Luo, Lixin; Zheng, Lin; Luo, Donghui; Zhao, Mouming
Abstract: Alcohol hydydrogenase (ADH) is a key enzyme that influences alcohol metabolism in vivo . Our previous study showed that chicken-derived tripeptide KPC could stabilize ADH in a dose-dependant manner. In this study, possible mechanism underlying how KPC could stabilize ADH was further investigated. Fluorescence quenching data showed that KPC induced a dynamic fluorescence quenching with a quenching rate constant value of 1.074 × 10 10  M −1 s −1, indicating a conformational change. Circular dichroism further suggested a possible transformation from α-helix (14.03%–13.90%) to random coil (31.98–33.04%) in ADH structure as affected by KPC (5 mmol/L). Molecular docking analysis predicted that KPC may bind to ADH through hydrophobic interaction and hydrogen bonds. Validation of ADH stabilizing activity of fragment peptides and amino acids from KPC implied the vital role of Cys residue to the bio-activity of KPC. These results indicated that KPC may stabilize ADH through peptide-enzyme interactions, and protect ADH against oxidative modification. Besides, a favorable absorption, distribution, metabolism, excretion, and toxicity (ADMET) profile of KPC was obtained using in silico assays. Overall, this study provided a comprehensive understanding on the interaction mechanism between KPC and ADH, and illustrated the potential applicability of KPC as drug or functional food ingredient. Highlights: KPC could interact with ADH and resulted in a dynamic fluorescence quenching. KPC may induced a more expanded structure of ADH. Hydrogen bonds and hydrophobic interaction contributed to the interaction between KPC and ADH. Cys residue play a vital role on the ADH stabilizing activity of KPC.